Seamus McNamus : the goat who would be king - Kurtz, Rob (Robert J.) (Worthwhile Books, 2009)
Seamus McNamus, according to local tradition, becomes king for three days at the local Puck Fair and tries to save the farm he lives on by convincing the town folk that the eggs, milk, and wool that come from the farm are worth buying.